Intellectual Property Management: Case Studies of Vietnamese SMEs - Le, Ha Thi-Thu; Luong, Trang Thi-Dai (International Journal of Business Strategy and Social Sciences, 2022)
Intellectual property is increasingly recognized as key contributor to business success. Meanwhile, in Vietnam, there exists a lack of evidence on how firms are managing their intellectual property strategically. With that being said, this paper aims to provide a systematic analysis of successful intellectual property management practices of Vietnamese small and medium-sized enterprises (SMEs). The authors redesign Intellectual Creation Cycle by Japan Patent Office, taking into account the unique management scenario among Vietnamese businesses. Then, we demonstrate patent and trademark management of six representative SMEs each in four steps: Creation, Registration, Utilisation and Protection. Data collection is based on in-depth interviews with directors of the selected companies. One of the most important findings is that it highlights collaboration between universities/public research institutions and businesses in an effort to develop high value-added products. Also, from the policy-making perspective, a number of lessons have also been drawn out: first, universities and public research institutions should be promoted to commercialise their research outputs; second, enhancement of finance scheme by the industry plays an important role in the IP commercialisation process. This paper thus provides strategic guidelines for Vietnamese SMEs in corporate IP management. It also proposes some practical insights for policy makers with respect to the promotion of IP among businesses, in particular SMEs for the purpose of economic growth.